KONSUMSI PROTEIN HEWANI SEBAGAI BENTUK PENCEGAHAN DAN PENANGANAN STUNTING PADA ANAK - Uus Usrotussachiyah; Ria Setia Sari; Febi Ratnasari (Nusantara Hasana Berdikari, 2022)
Stunting is a growth failure that is a global problem in today's world especially in developing countries. The process of failure has been linked to the chronic unsatisfying of nutrients, which include the kelp of animal protein, which provides a high concentration of protein consumption in Indonesia The formation of a bone matrix in the child. The purpose of the literature review is to Knowing specifics and analyzing the articles related to animal protein intake as a precautionary or stunting treatment for children. The method used was the search for relevant articles on the topic of discussion Using Google help, mozila fire fox and chrome with database access An e-repellent. The results of analysis of the article indicate that the consumption of animal protein (milk, eggs, fish, eels and birds) is significantly beneficial in improving stunted growth and can prevent children from developing stunting that results in decreased prevalence Stunting children. Based on the avaible data intake of animal protein, it has significant benefits to HAZ of child.